Moderating the Influence of Online Customer Reviews and Online Customer Ratings on Purchase Intention with Live Streaming - Algifani, M. Gaza; Faerrosa, Lady; Widiyasti, Baiq Dinna (Postgraduate, University of Mataram, 2025)
In the past year, the Lazada application has experienced a significant decline in the number of visitors and purchases, suspected to be caused by poor consumer experience that has reduced consumer purchase intentions on the Lazada application. Product reviews and ratings on the Lazada application are often questionable in their credibility, either because the review sources are unreliable or because there is a discrepancy between product ratings and product quality. This study aims to analyze the influence of online customer reviews and ratings on purchase intention and to see the moderation ability of live streaming on the influence of both variables on purchase intention. The method used is a quantitative method with the Structural Equation Model-Partal Least Square (SEM-PLS) data analysis technique. Respondents in this study were 160 Lazada application users in the city of Mataram who had made purchases in the past year and had watched live streaming. Data processing used Smart PLS. The results of this study indicate that Online Customer Reviews and online customer ratings have a positive and significant effect on Purchase Intention. In addition, live streaming is confirmed to significantly strengthen the influence of online customer reviews and online customer ratings on purchase intention. These findings can help Lazada improve consumer experience and increase the credibility of product reviews and ratings, which can ultimately increase consumer purchase intentions. In addition, this study also provides insight into how marketing strategies, such as live streaming, can influence purchasing decisions on e-commerce platforms.